2011
DOI: 10.5194/hessd-8-2477-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of agricultural intensification through upscaling of suitable rainwater harvesting technologies in the upper Ewaso Ng'iro North basin, Kenya

Abstract: Changes in land cover and land use can lead to significant impacts to hydrology by affecting the amount of runoff, soil moisture and groundwater recharge over a range of temporal and spatial scales. However, hydrologic effects of these changes are still an unknown at watershed scale. Moreover, predicting the effects of land cover/use and climate change on hydrological cycle has remained a major challenge. This is because of the complexity and uncertainty of future climate changes making it difficult to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Water resources are inextricably linked with climate, and the prospect of global climate change has serious implications for future water resources and regional development [1,2,[30][31][32]. The large variation in the spatial and temporal distribution of water resources in the Sokoto Rima River basin, the Didessa sub-basin, the Niger River basin, etc., will make the consequences of water scarcity even more severe unless DSM strategies are implemented which prove to be effective in minimizing the future growth in water demand and basin surface runoff.…”
Section: Resilience and Reliability Of Water Systemsmentioning
confidence: 99%
“…Water resources are inextricably linked with climate, and the prospect of global climate change has serious implications for future water resources and regional development [1,2,[30][31][32]. The large variation in the spatial and temporal distribution of water resources in the Sokoto Rima River basin, the Didessa sub-basin, the Niger River basin, etc., will make the consequences of water scarcity even more severe unless DSM strategies are implemented which prove to be effective in minimizing the future growth in water demand and basin surface runoff.…”
Section: Resilience and Reliability Of Water Systemsmentioning
confidence: 99%
“…According to Mutiga et al (2011), grasslands occupied 18% of the basin area in 2003 (down from 20.5% in 1987), while according to CETRAD (2014) grassland covered 43%. Mutiga et al (2011) also included a 'bareland' land use category (covering 24.1%), however, which was not considered by CETRAD (2014). We, therefore, used only the grassland category, estimated to cover 43% of the area.…”
Section: Grasslands and Barelandmentioning
confidence: 99%
“…According to Mutiga et al (2011), surface waters cover 1% of the basin or 15 200 ha. Ngigi et al (2008) reported that water bodies cover 0.04% of the Naro Moru sub-basin.…”
Section: Horticultural Dams and Other Surface Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Various authors have studied the effects of abstractions upstream on the discharge of the Ewaso Ng'iro River, with some using models to predict the effects of these abstractions on downstream discharge [12]. While such models are useful to gain understanding in systems behavior, we decided to present in this paper the reported permitted abstractions and estimates of the demand for water to give an impression of the magnitude of the abstractions in the upper part of the catchment.…”
Section: Discharge Of the Ewaso Ng'iro River Into The Swampmentioning
confidence: 99%